Pre-exposure to Candida albicans induce trans-generational immune priming and gene expression of Musca domestica - Li, Zhongxun; Jia, Lina; Yi, Hong; Guo, Guo; Huang, Li; Zhang, Yingchun; Jiao, Zhenlong; Wu, Jianwei (Frontiers in Microbiology, 2022)
Insects have the phenomenon of innate immune memory by which they can have enhanced protection on reinfection with the same pathogen, and this immune protection can be passed on to their offspring, which is defined “Trans-generational immune priming (TGIP)”. But whether housefly possess TGIP is still unclear. Therefore, we used housefly as the insect model and Candida albicans as the pathogen to explore whether housefly is capable of eliciting TGIP, and RNA sequencing (RNA-seq) was performed to explore the molecular mechanism of TGIP of housefly. We found that housefly possess TGIP, adults pre-exposed to heat-killed C. albicans could confer protection to itself and its offspring upon reinfection with lethal dose of C. albicans. RNA-seq results showed that 30 and 154 genes were differentially expressed after adults primed with heat-killed C. albicans (CA-A) and after offspring larvae challenged with lethal dose of C. albicans (CA-CA-G), respectively. Among the DEGs, there were 23 immune genes, including 6 pattern recognition receptors (PRRs), 7 immune effectors and 10 immunoregulatory molecules. More importantly, multiple DEGs were involved in Toll signaling pathway and Phagosome signaling pathway, suggesting that Toll signaling pathway as well as Phagocytosis might play important roles in the process of TGIP of housefly to C. albicans. Our results expanded on previous studies, and provided parameters for exploring the mechanism of TGIP.